2015
DOI: 10.18632/oncotarget.4925
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA methylation and gene expression patterns in purified, uncultured human liver cells and activated hepatic stellate cells

Abstract: Background & Aims: Liver fibrogenesis -scarring of the liver that can lead to cirrhosis and liver cancer -is characterized by hepatocyte impairment, capillarization of liver sinusoidal endothelial cells (LSECs) and hepatic stellate cell (HSC) activation. To date, the molecular determinants of a healthy human liver cell phenotype remain largely uncharacterized. Here, we assess the transcriptome and the genome-wide promoter methylome specific for purified, non-cultured human hepatocytes, LSECs and HSCs, and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 73 publications
4
46
0
Order By: Relevance
“…HSC activation can be suppressed by inhibitors of DNMT1 (e.g., 5-Aza-2′-deoxycytidine) and enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2), a polycomb group-protein complex catalyzing trimethylation of histone 3 lysine 27 (H3K27me3) (e.g., 3-deazaneplanocin), supporting their regulatory role in the activation [256258]. DNMT1-mediated DNA hypermethylation of phosphatase and tension homolog (PTEN) leads to HSC activation [259].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…HSC activation can be suppressed by inhibitors of DNMT1 (e.g., 5-Aza-2′-deoxycytidine) and enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2), a polycomb group-protein complex catalyzing trimethylation of histone 3 lysine 27 (H3K27me3) (e.g., 3-deazaneplanocin), supporting their regulatory role in the activation [256258]. DNMT1-mediated DNA hypermethylation of phosphatase and tension homolog (PTEN) leads to HSC activation [259].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Important epigenetic changes are induced by ROS in the HSCs, including chromatin remodeling by histone modification, DNA methylation and gene silencing by microRNAs (miRs) [158]. In-vitro and in-vivo approaches have demonstrated that HSCs show a global demethylation of fibrogenic genes during transdifferentiation into myofibroblasts, which is associated with liver fibrosis development [159][160][161].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Immunostaining of WT1, MIIA, and LHX2 also confirmed the correct cell fate induction in the presumptive STM cells ( Figure 3A). Global gene array analysis suggested iPSC-STM signatures showed a remarkable shift toward reported human adult hepatic mesenchymal cell signatures (Asahina et al, 2009(Asahina et al, , 2011El Taghdouini et al, 2015) ( Figure 2G). We previously demonstrated that one function of mesenchymal cells in LB generation is myosin-IIAdependent self-condensation.…”
Section: Resultsmentioning
confidence: 99%
“…Error bars represent the SD of values obtained from three independent experiments (n = 4). (G) Hierarchical clustering with AdHep mesenchymal cell signatures in iPSC-STM (Asahina et al, 2009(Asahina et al, , 2011El Taghdouini et al, 2015). directly anastomosed with mouse CD31 endothelial cells (Figure 3H) and were surrounded by iPSC-STMs at a perivascular location ( Figure 3I).…”
Section: Resultsmentioning
confidence: 99%